2022
DOI: 10.1101/2022.11.13.516348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultivation and Fluorescent in situ hybridization suggest that some shipworm species acquire endosymbiotic bacteria through indirect horizontal transmission

Abstract: Beneficial microbial symbionts provide essential functions for their host from nutrients to defense against disease. Whether hosts acquire their symbionts directly from parents (vertical transmission) or by sampling from the environment (horizontal transmission) can have dramatic impacts on host adaptability and, in the case of ecosystem engineers, ecosystem health. Wood-boring bivalve mollusks (Teredinidae shipworms) act as ecosystem engineers in marine environments, creating habitat out of submerged wood for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that in one shipworm species, Bankia setacea , bacterial symbionts are acquired through vertical transmission directly from parents ( 90 ). However, a recent report demonstrated that juveniles of other species such as Lyrodus pedicellatus and/or Teredo bartschi are initially free of bacterial symbionts and acquire them through horizontal transmission from the environment ( 91 ). T. turnerae has been isolated from these species, and the genome sequence of T. turnerae does not exhibit features typically observed in obligate intracellular symbionts, such as reduced genome size, GC content, and loss of genes involved in the core metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in one shipworm species, Bankia setacea , bacterial symbionts are acquired through vertical transmission directly from parents ( 90 ). However, a recent report demonstrated that juveniles of other species such as Lyrodus pedicellatus and/or Teredo bartschi are initially free of bacterial symbionts and acquire them through horizontal transmission from the environment ( 91 ). T. turnerae has been isolated from these species, and the genome sequence of T. turnerae does not exhibit features typically observed in obligate intracellular symbionts, such as reduced genome size, GC content, and loss of genes involved in the core metabolism.…”
Section: Discussionmentioning
confidence: 99%